2006
DOI: 10.1007/s11481-006-9035-1
|View full text |Cite
|
Sign up to set email alerts
|

Defining and Evaluating HIV-Related Neurodegenerative Disease and Its Treatment Targets: A Combinatorial Approach to Use of Cerebrospinal Fluid Molecular Biomarkers

Abstract: There are a number of reasons that the accomplishments of clinical trials related to HIV-related neurodegenerative disease (HRND) and the AIDS dementia complex (ADC) have had such limited impact on clinical practice. These include: rapid evolution and progress in the treatment of systemic HIV infection that has quickly outpaced neurological efforts and has markedly reduced disease incidence; ethical constraints that (rightly) demand neurologically compromised patients receive the best available treatment befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 27 publications
1
42
0
Order By: Relevance
“…The CSF/plasma albumin ratios were calculated as a measure of blood-brain barrier (BBB) disruption, while CSF WBC levels were measured as a simple marker of inflammation and inflammatory-cell migration into the CNS. Additionally, the level of CSF neopterin, a pteridine produced by activated macrophages and associated with intrathecal immunoactivation, is elevated in HIV-infected subjects and is characteristically particularly high (Ͼ22 nmol/ liter) in those with HIV-1-associated dementia (3,17). All 17 subjects were enrolled within the first year of infection, with a median at baseline of 143 days p.i.…”
Section: Resultsmentioning
confidence: 99%
“…The CSF/plasma albumin ratios were calculated as a measure of blood-brain barrier (BBB) disruption, while CSF WBC levels were measured as a simple marker of inflammation and inflammatory-cell migration into the CNS. Additionally, the level of CSF neopterin, a pteridine produced by activated macrophages and associated with intrathecal immunoactivation, is elevated in HIV-infected subjects and is characteristically particularly high (Ͼ22 nmol/ liter) in those with HIV-1-associated dementia (3,17). All 17 subjects were enrolled within the first year of infection, with a median at baseline of 143 days p.i.…”
Section: Resultsmentioning
confidence: 99%
“…Autopsy and neuroimaging studies have identified that HIV-1 can localize in the basal ganglia and hippocampus [13,14], even during the first weeks of infection [15]. Potent ART can reduce the HIV-1 level in blood and cerebrospinal fluid (CSF) below the quantification limit of commercially available assays, but HIV-1 might continue to replicate at low levels, increasing the risk for viral compartmentalization in the CNS [16]. Persistent low-level HIV-1 replication could also lead to glial activation and neuronal injury.…”
mentioning
confidence: 99%
“…It has been proposed that a combination of markers be used in ongoing trials. 1,2 This approach would combine indicators of neuronal damage (eg, NFL), HIV activity (eg, HIV-RNA), and neuroinflammation (eg, MCP-1) to create a combined picture of ongoing CNS activity and disease risk.…”
Section: Resultsmentioning
confidence: 99%
“…Combinations of markers may be useful in caring for patients with HIV, 1 but much work remains to validate these biomarkers with their clinical correlates. 2 The translation of this work into day-to-day patient care is an ongoing endeavor. A particular challenge is to develop biomarkers that can be used in resource-poor settings, where the majority of disease burden lies.…”
Section: Introductionmentioning
confidence: 99%